Cultural identity in local literary narratives: A semiotic analysis of the novel Entrok and Laut Bercerita - Senen, Ikram; Artanti, Yeni; Azhari; Tianusad, Marseilles (Universitas Mulawarman, 2025)
This research examines the ways in which Indonesian local literary narratives formulate and perpetuate cultural identity amid globalizations. It specifically examines the symbolic representations in Entrok by Okky Madasari and Laut Bercerita by Leila S. Chudori through Roland Barthes’ semiotic framework, focusing on denotation, connotation, and myth. The study utilizes a qualitative text analysis approach, relying on comprehensive readings of the novels and supplemented by secondary literature. Symbols like the Entrok (a traditional Javanese brassiere) and the sea are identified and coded using a deductive method based on Barthes’ categories. The results show that Entrok criticizes patriarchal control and class-based oppression by changing the meaning of everyday objects. “Laut Bercerita,” on the other hand, shows the sea as a sacred place of ecological awareness and collective resistance. These symbols function on various semiotic levels, demonstrating literature’s role as a medium for cultural negotiation and ideological critique. The research finds that Indonesian local literature is essential for maintaining cultural resilience and identity development, providing educators and policymakers with effective methods to enhance cultural awareness through storytelling.